1988
DOI: 10.2134/agronj1988.00021962008000060019x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Maize to Plant Population Density. II. Reproductive Development, Yield, and Yield Adjustments

Abstract: Plant population density (PPD) exerts a strong influence on maize (Zea mays L.) growth and grain yield. Most PPD studies have usually confounded plant number with spatial arrangement, since row width remained constant and only spacing between plants in row was varied. This study used a systematic design (fan) to observe the effect of 15 PPD (0.8∓15.4 plants m−2) on maize reproductive growth in constant spatial arrangement on Lake fine sand (hyperthermic, coated Typic Quartzipsamments) at Gainesville, FL (29°38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
58
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 13 publications
10
58
0
5
Order By: Relevance
“…Kixxo. Similar results were reported by Machul [41], Tetio-Kagho and Gardner [42], and Begna, Hamilton, Dwyer, Stewart, & Smith [43] who found that increased seeding rates led to a decrease in the weight, length and diameter of ears as well as in the weight and number of kernels per ear in maize grown for grain.…”
Section: Discussionsupporting
confidence: 86%
“…Kixxo. Similar results were reported by Machul [41], Tetio-Kagho and Gardner [42], and Begna, Hamilton, Dwyer, Stewart, & Smith [43] who found that increased seeding rates led to a decrease in the weight, length and diameter of ears as well as in the weight and number of kernels per ear in maize grown for grain.…”
Section: Discussionsupporting
confidence: 86%
“…However, although at low plant densities, increasing the number of plants per unit area results in proportional increments in crop yield, above certain plant densities the marginal increment of yield with increased population decreases, approaching zero, and may eventually become negative (Tetio-Kagho, 1988;Sangoi et al, 2002). The results presented here suggest that enhanced PHYB levels could be used in breeding programs to shift optimum crop densities to higher values.…”
Section: Discussionmentioning
confidence: 69%
“…For example, the effect of plant density on leaf area expansion through two parts i.e., lamina length and lamina width, the first being consistently decreased in both lower and upper phytomers [36] whereas the second being increased in lower phytomers and decreased in upper phytomers [37]. Increasing panting density accelerated leaf senescence [38], increased the shading of leaves [18], and reduced the net assimilation of individual plants.…”
Section: Plant Density Effect On Canopy Morphology Of Maize Cropmentioning
confidence: 99%